Implementasi Sistem Pengelolaan Dokumen pada PT Sri Aneka Karyatama - Juwita Maya sari; Meiriyama Meiriyama (Jurnal Teknologi Sistem Informasi, 2023)
PT Sri Aneka Karyatama, also known as PT.SAK, is a company that offers construction, engineering, supply and cleaning services. Founded in 1987, this company is a subsidiary of PT. Pupuk Sriwidjaja and has 26 years of experience in various business fields, with the main focus on building maintenance and cleaning services. Even so, PT. Sri Aneka Karyatama experienced problems in archiving letters, such as data collection, storage, and data corruption. Therefore, to overcome this problem, a new information system was created which included the process of inputting incoming and outgoing mail, user input, mail search, and mail reporting. The methodology used is an iterative methodology, and users of the new information system are HRD, managers and directors of PT. Sri Aneka Karyatama. The result of creating this new information system is to help simplify the incoming and outgoing mail process, save time, and reduce the obstacles experienced by company staff.